Efficacy and Safety of the Traditional Herbal Medicine, Gamiguibi-tang, in Patients With Cancer-Related Sleep Disturbance: A Prospective, Randomized, Wait-List-Controlled, Pilot Study. (June 2018) - Lee, Jee Young; Oh, Hye Kyung; Ryu, Han Sung; Yoon, Sung Soo; Eo, Wankyu; Yoon, Seong Woo
Background: Sleep disturbance is the second most bothersome symptom in patients with cancer, and it can significantly impair their quality of life. The aim of this study was to investigate the efficacy and safety of the traditional herbal medicine Gamiguibi -tang (GGBT) in patients with cancer-related sleep disturbance.Methods: We conducted a prospective, randomized, wait-list-controlled, open-label pilot clinical trial on cancer-related sleep disturbance. Patients with cancer experiencing poor sleep quality with a Pittsburgh Sleep Quality Index of at least 6 were randomly assigned to the GGBT and wait-list groups to receive GGBT and conventional care, respectively, for 2 weeks. The primary endpoint was the Insomnia Severity Index (ISI) score. Fatigue, depression, and cognitive impairment were assessed as the secondary endpoints by using the Brief Fatigue Inventory (BFI), Beck Depression Inventory (BDI), and Montreal Cognitive Assessment (MoCA).Results: Thirty participants who met the eligibility criteria were enrolled. Sleep disturbance assessed using the ISI improved significantly more in the GGBT group than in the wait-list group (−5.5 ± 4.4 vs 0.1 ± 1.1, P < .001). Fatigue level determined using the BFI also improved significantly more in the GGBT group than in the wait-list group (−0.8 ± 0.8 vs 0.0 ± 0.3, P = .002). The BDI and MoCA scores showed no significant changes. Adverse events were reported in two patients in the GGBT group and consisted of mild dyspepsia and mild edema.Conclusion: GGBT may be a potential treatment option for cancer-related sleep disturbance. Further research is needed to investigate the efficacy and safety of GGBT.